Evaluation of immunity status to routine vaccination in pediatric liver transplant candidates - Dehghani, Seyed Mohsen; Shakiba, Mohammad Ali; Ziaeyan, Maziyar; Imanieh, Mohammad Hadi; Haghighat, Mahmood; Sedaghat, Majid; Alborzi, Abdolvahab; Malek-Hosseini, Seyed Ali (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Generally, prevention of infections by vaccination is the least invasive and most cost-effective approach to reduce the incidence of infections and the morbidity and mortality in transplant recipients. Genetic diversity and different liver disease among patients contributes to variability in immune responses to vaccines and pathogens. The aim of this study was to evaluate immunity status to different vaccinated organisms in pediatric liver-transplant candidates. Materials and Methods: The vaccination charts of 90 patients who were referred to Organ Transplant Center of Shiraz University of Medical Sciences were reviewed and compare with National Immunization Program recommendation, after that 10 mL blood was drawn from these patients for serologic studies by ELISA. Results: Eighty percent of the patients had protective antibody titers for poliomyelitis, 65.6% for rubella, 62.3% for diphtheria, 60% for tetanus, 57.7% for pertussis, 55.5% for measles, 42.2% for hepatitis B and 36.7% for mumps. Conclusion: Overall seroconversion rates were not satisfactory for many infections that may be due to lower rate of vaccination or even the underlying liver disease that interfere with optimal immunogenecity of vaccination. Therefore, vaccination charts should be periodically reviewed and updated, also repeated measurements of serum antibodies and appropriate revaccination if titers decline is recommended to prevent the vaccine-preventable disease in liver transplant candidates after transplant.